Dvodimenzijsko modeliranje gibanja drobirskega toka v Logu pod Mangartom kot primer nenewtonske tekočine - Četina, Matjaž (Strojniški vestnik, 2003)
Mathematical models have been used for simulations of the landslide (debris flow) below Stože that occured in November 2000, and destroyed part of the village of Log pod Mangartom. The one-dimensional model, DEBRIFID, was first used for simulations along the upper part of the affected region, where the debris flow was mainly in a narrow canyon. Hydrographs of the debris-flow discharge at the upstream end of the affected village of Log pod Mangartom were thas determined for possible future landslides. Two-dimensional simulations of the debris flow in the village were carried out using two models: PCFLOW2D, developed at the University of Ljubljana, and a commercial model FLO-2D. The three models were succesfuly calibrated using field measurements of the debris-flow inundation limits, taking into account the results of geo-mechanical laboratory experiments. The sensitivity analysis of the two-dimensional model PCFLOW2D with different grid sizes and two different out flow boundary conditions was also made. The validity of the quadratic equation expressing the resistance of the non-Newtonian Bingham plastic fluid model was roughly confirmed, even for changing flow regimes. ...
Keywords: tokovi drobirski; modeli matematični; tekočine nenewtonske; urejanje hudournikov; nenewtonske tekočine; matematični modeli; drobirski tok